Prediction of water inflow and analysis of surrounding rock stability in unfavorable geological mountain tunnel - Chen, Yunjuan; Liu, Mengyue; Su, Mengzhen; Ding, Mingxu; Li, Haolin; Jing, Yi (Frontiers in Earth Science, 2024)
During the construction of a mountain tunnel, water inflow and rock instability are common occurrences due to unfavorable geological conditions, posing serious threats to construction safety. This study focuses on a proposed mountain tunnel and employs multiple formulas to predict potential water inflow during excavation. Based on the amount of water inflow and deformation of surrounding rocks, comprehensive determinations are made for the thickness of grouting rings and permeability coefficients. The results demonstrate that: 1) Different formulas yield slightly varied outcomes but overall trends remain consistent; considering various calculations, the normal water inflow for this tunnel is approximately 115.5908×103 m3/d with a maximum at 210.9100×103 m3/d 2) Increasing grouting ring thickness or decreasing permeability coefficient can effectively reduce water inflow, but the reduction range is gradually narrowed. 3) Pre-grouting curtains have an evident effect in enhancing stability; however, their effectiveness decreases with increased thickness. 4) Taking into account both safety and economic factors, it is recommended that the grouting ring thickness be set at 8 m with a permeability coefficient equaling one 100th that of surrounding rocks for this tunnel project.